Upconversion luminescence enhancement of Yb3+, Nd3+ sensitized NaYF4 core–shell nanocrystals on Ag grating films. Issue 8 (11th December 2014) - Xu, Wen; Song, Hongwei; Chen, Xu; Wang, Haiyu; Cui, Shaobo; Zhou, Donglei; Zhou, Pingwei; Xu, Sai
Abstract : The UCL enhancement of NaYF4 :Yb 3+, Tm 3+ @NaYF4 :Yb 3+, Nd 3+ core–shell NCs resulting from Ag grating structures provides a novel insight for improving UCL. Abstract : Here, we report the wavelength-dependent and angle-dependent upconversion luminescence (UCL) enhancement of NaYF4 :Yb 3+, Tm 3+ @NaYF4 :Yb 3+, Nd 3+ core–shell nanocrystals (NCs) resulting from Ag grating structures, which provides a novel insight for improving UCL.